2001
DOI: 10.1007/s004310100816
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Omenn syndrome

Abstract: Omenn syndrome is a fatal disease if untreated. The mortality may be reduced when diagnosis is established early and treatment is initiated rapidly by using early compatible bone marrow transplantation or cord blood stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
101
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 33 publications
2
101
0
5
Order By: Relevance
“…13 A recent review analyzed the outcome of 68 OS patients reported in the literature between 1965-1999. 2 The overall mortality of 41 evaluable patients was 59%; in particular, 69% of the untransplanted patients died within the first year of life, whereas mortality of the 28 transplanted OS patients was shown to be 46%.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…13 A recent review analyzed the outcome of 68 OS patients reported in the literature between 1965-1999. 2 The overall mortality of 41 evaluable patients was 59%; in particular, 69% of the untransplanted patients died within the first year of life, whereas mortality of the 28 transplanted OS patients was shown to be 46%.…”
mentioning
confidence: 96%
“…1 Other common symptoms include diarrhea, alopecia, and failure to thrive. 2 Occasionally, a similar clinical phenotype may be noticed in other immunodeficiency syndromes, [3][4][5][6] and particularly in SCID with maternal T-cell engraftment.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…OS features a specific spectrum of clinical manifestations including erythroderma, lymphadenopathy, and frequent severe infections (1,2). Mutations in RAG1 and RAG2 and less frequently in the DCLRE1C gene, encoding the Artemis protein, or other loci have been identified in OS patients (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…10 Omenn-like syndrome is the engraftment of maternal T-cells in a child with a T-SCID, which is clinically reminiscent of Omenn syndrome. [11][12] Case report…”
mentioning
confidence: 99%